"Reforming the law of intestate succession in a legally plural Ghana". Issue 1 (2nd January 2019) - Hammond, Ama
Abstract: There has been minimal compliance with Ghana's Intestate Succession Act, 1985, (PNDC Law 111) especially by communities in rural areas whose lives are governed almost exclusively by customary law. This is because the state and customary legal systems have failed to reconcile their perceptions of law and legal responsibilities. Drawing on legal pluralism as a practical guiding framework for analyzing the relationship between states and customary legal systems, and focusing on the law of intestate succession, I argue that in order for legal reforms to be embraced, especially by rural dwellers, the state must adopt what may be termed, the mutual concession approach to legal reforms, a structured and principled discretionary approach that seeks to balance the valued interests of both legal systems, and which promises to be more agreeable to rural dwellers in ways that ensure compliance with state law.